Nyelamak Dilaok : Sebuah Tradisi Selametan Masyarakat Pesisir Tanjung Luar Lombok Timur - Syahdan Syahdan (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2021)
Nyelamak dilaok is a culture that has existed 400 years ago brought by sea travelers from Sulawesi. This tradition is carried out in the village of Tanjung Luar, Keruak District, East Lombok Regency in the month of Rajab in the Hijri calendar by floating the head of a buffalo on a cluster of rocks in the Tanjung Luar sea. The purpose of this study was to find out how the procedure for implementing nyelamak was carried out from beginning to end. This study also aims to determine the implications of nyelamak dilaok on the community's aqidah, especially for the students of TPQ Al-Mujaddid as the next generation. The data collection procedure used in this study is to collect data through interviews, observation, recording and documentation. Sources of data used are informants who are involved and understand about the tradition, namely traditional leaders, community leaders, religious leaders, village governments, the general public, students of TPQ Al-Mujaddid and books that support the research. While the data analysis method used is a description in the form of a narrative. From the results of the study it can be concluded that if viewed from a social perspective, the tradition of nyelamak dilaok has noble cultural values, but behind it all, in its implementation, it contradicts the teachings of Islam which has implications for the aqidah of TPQ Al-Mujaddin students